Cognitive Therapy Decrease the Level of Depression - Ah. Yusuf; Hanik Endang Nihayati; Zaenal Abidin (Universitas Airlangga, 2008)
Introduction: Aging is a natural process in individuals. Most of the elderly have problems in dealing with this natural process. Lost of occupation, friends and loneliness may result in depression in this age group. Cognitive therapy changes pessimistic idea, unrealistic hopes and excessive self evaluation may result and justify depression. Cognitive therapy may help elderly to recognize the problem in life, to develop positive objective of life and to create more positive personality. The aimed of this study was to analyze the effect of cognitive therapy to reduce the level of depression. Method: This study was used a pre experimental pre post test design. Sample were 10 elderly people who met to the inclusion criteria. The independent variable was cognitive therapy and dependent variable was the level of depression in elderly. Data were collected by using Geriatric Depression Scale (GDS) 15, then analyzed by using Wilcoxon Signed Rank Test with significance levelα≤0.05. Result: The result showed that cognitive therapy has an effect on reducing depression with significance level p=0.005. Discussion: It can be concluded that cognitive therapy was effective in reducing depression level in elderly. Further studies are recommended to analyze the effect of cognitive therapy on decreasing anxiety in elderly by measuring cathecolamin.